A service evaluation of specialist nurse telephone follow-up of bowel cancer patients after surgery. (24th October 2019) - Mole, Guy; Murali, Mayur; Carter, Sarah; Gore, David; Broadhurst, Jack; Moore, Tim; Vickers, Philip; Miles, Andrew
Abstract : Introduction: the NHS Long Term Plan has called for a reduction in the number of outpatient appointments to reduce pressure on hospital services and increase ease of access for patients. This article presents a service evaluation of an innovative, nurse-led telephone follow-up service for a group of elective bowel cancer patients following surgery. Methods: the records of patients who underwent surgery over a 2-year period were accessed to determine the number of telephone follow-ups and other investigations. This was used to model the potential cost saving for commissioners against traditional clinic follow-up. Patient satisfaction was assessed by the European Organisation for Research and Treatment of Cancer questionnaire on Outpatient Satisfaction in 30 patients. Results: feedback on the service was overwhelmingly positive, with patients praising the care received from the specialist nurses, but also commenting on increased continuity of care, ease of access and convenience. The service also potentially creates significant savings for commissioners as the agreed tariff for nurse telephone follow-up is significantly less than the outpatient tariff. Discussion: this innovative follow-up system is well liked by patients and should provide savings for commissioners. The hospital also benefits from an increase in capacity to see new or more unwell patients, and a reduction in carbon emissions. Such a service, however, is dependent on people, and although it has functioned effectively in this department for approximately 20 years, it would only be generalisable to other units if staff had appropriate expertise.